Intrauterine Transfusion Complicated by Umbilical Artery Thrombosis - Roopali V. Donepudi; Kenneth J. Moise (Hindawi Limited, 2019)
Background. Fetal anemia results from several conditions; however intrauterine transfusion (IUT) remains the treatment for severe cases. The complications of this procedure are rare and yet can result in preterm delivery or fetal death. Case. 31 y/o G3P2002 with Rh alloimmunization underwent IUT from 19 to 35 weeks. Umbilical artery thrombosis was noted after her 5th IUT. Further transfusions were performed without any complications and she delivered a full term male infant with APGARS of 8 and 9 at 1 and 5 minutes, respectively. Conclusion. The complication of umbilical artery thrombosis is unusual and the optimal management is unclear. We report such a case and propose that the presence of Hyrtl's anastomosis near the placental cord insertion may explain the reassuring fetal status throughout the pregnancy.